KOMPETENSI PROFSIONAL GURU SOSIOLOGI YANG BERSERTIFIKASI DI SMAN 1 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Sari, Sisry Purnama (Pendidikan Sosiologi, 2014)
This research discuss abaut the professional competence of sociology teacher certificationin SMAN 1 Enam Lingkung Padang Pariaman Regency, in teaching learning process, sociologyteacher just focuses on sources book, not clear explanation and the teacher stiil use some sentencessame with books not use their own exlanation. So, the Studens get difificulties to understand thatlesson. The purpose of this research was to describe the professional competence of sociologyteacher certification in SMAN 1 Enam Lingkung Padang Pariaman Regency. The research usedchangable, theory and employed a descriptive qualitative study. The participants of this researchwas sociology teacher certification in SMA that lesson. Which were taken by using porposivesampling technique. The research esed primer and secondery data. To gather the data, thereseacher used observation and interview document study. Unit analysis data was the group ofsociology teacher certification and the students of SMAN 1 that lesson. The data analysis used theparticiple of miles and huberman. Based on the result of this research, it was concluded that theprofessional competence of sociology teacher in SMAN 1 that lesson was still low. It is provedthat sociology teacher were not yet implement the five of professional competence indicators,included, a) comprehed the lesson for teaching, b)comprehend standars of competence andstandars cotents of lesson as suitable with regulation in KTSP, c)comrehend structure, conceptr,method of science in the lesson of teaching material, d) comprehend the correlation of lessonconcept, e) implement the science concepts in daily life. Referring of the five concept, it was 2indicators that have implemented.